Marriner S. Eccles and the 1951 Treasury-Federal Reserve Accord: Lessons for Central Bank Independence - Thorvald Grung Moe (Norges Bank, 2014)
The 1951 Treasury-Federal Reserve Accord is an important milestone in central bank history. It led to a lasting separation between monetary policy and the Treasury's debtmanagement powers and established an independent central bank focused on price and macroeconomic stability. This paper revisits the history of the Accord and elaborates on the role played by Marriner Eccles in the events leading up to the Accord. As chairman of the Board of Governors since 1934, Eccles was also instrumental in drafting key banking legislation that enabled the Federal Reserve System to assume a more independent role following the Accord. The global financial crisis has generated renewed interest in the Accord and its lessons for central bank independence. This paper shows that Eccles' support for the Accord-and central bank independence-was clearly linked to the strong inflationary pressures in the US economy at the time, and that he was equally supportive of deficit financing in the 1930s. This broader interpretation of the Accord holds the key to a more balanced view of Eccles's role at the Federal Reserve, where his contributions from the mid-1930s up to the Accord are seen as equally important. Accordingly, the Accord should not be viewed as the final triumph of central bank independence, but rather as an enlightened vision for a more symmetric policy role for central banks, with equal weight given to fighting inflation and preventing depressions.
hdl:11250/2495979
Keywords: B31; E52; E58; E63; N12; 330; Marriner Eccles; central banking; monetary policy; fiscal policy